The Contribution of Siwalima Values as a Philosophy of Life to Preserve the Plural Society in the Moluccas - Henky H. Hetharia (JICSA : Journal of Islamic Civilization in Southeast Asian, 2014)
Local wisdom is a cultural product and strategy of local society that responds problems they are facing. The Moluccan people have a local wisdom, which is called Siwalima. Siwalima is a culture and philosophy of life of the Moluccan people that has universal values. The value is an ultimate value of the Maluccan people. It contributes and becomes an integrating force to maintain and unite the plural / multicultural society (the whole ethnic of Indonesia) in the Moluccas at present and in the future. Therefore, strategic steps have to be taken to function for the contribution. As a matter of fact, the focus of this research and article is Siwalima with its values as a philosophy of life of the Moluccan people. This research is done by having a qualitative approach.